Infant Feeding Practices with Oral Health Implications among Suburban Mothers of Tanzania - Shariff Mbawalla, Hawa; Majid, Shadia (International Journal of Child Health and Nutrition, 2017)
Background: Behaviours around infants feeding influence both nutritive value and the detrimental effects of the infant feeding. Aim: The study aimed to determine infant feeding practices with implication to child’s oral health and examine the related socio-demographic factors. Materials and Methods: A cross-sectional study among mothers of the infants who were attending RCH clinics in suburban areas of northwest Tanzania. Cluster sampling technique was used to obtain the participants and a structured questionnaire was used to interview the mothers. Frequency distributions and cross-tabulations were used for analysis and reported as proportions and identified differences between the comparative socio-demographic categories. Results: Study involved 213 mother-infant pairs; infants’ mean age was 7.22 ± 3.48 months and 53.1% were female babies. Almost all (94.6 %) the infants were breastfed and 75.3% of infants under six months of age were exclusively breastfeeding. In infants age older than six months, 32.6% of mothers reported to have initiated complementary food before the baby turned six months and that sugar sweetened foods were mostly used (68.1%) complementary foods. Higher proportion of mothers who had secondary school education or beyond (43.4%) reported to have initiated complementary food before the recommended age than their counterparts. Mothers who were employed reported to mostly (74.5%) use sugar sweetened complementary foods as compared to unemployed mothers. Conclusion: Infants of this community were mostly breastfed and initiated complementary feeding earlier than recommended time. Employed mothers and those with secondary education or above tended to have unfavorably infant feeding practices than their comparative groups.